Infections In Hospitalized Patients With Psoriasis In A Skin Referral Hospital - Nafiseh Zaredar; Hamidreza Mahmoudi; Tahereh Soori; Amir Teimourpour; Kamran Balighi; Ali Salehi Farid; Maryam Daneshpazhooh (Mattioli1885, 2023)
Introduction: Psoriasis and its treatments may predispose patients to various infections. This is considered one of the most significant complications in patients with psoriasis.  Objectives: In the present study, we aimed to determine the prevalence of infection in hospitalized psoriasis patients and its relationship with systemic and biologic treatments. Methods: All hospitalized patients with psoriasis from 2018 to 2020 in Razi Hospital in Tehran, Iran, were studied and cases of infection were recorded. Results: Overall, 516 patients were studied and 25 types of infection in 111 patients were found. The most common types of infection were pharyngitis and cellulitis, followed by oral candida, urinary tract infections, common cold, fever of unknown origin, and pneumonia. Female sex and pustular psoriasis were significantly associated with infection in psoriatic patients. Those patients who received prednisolone had a higher risk of infection, and those under treatment with methotrexate or infliximab had a lower risk of infection. Conclusion: Overall, 21.5% of psoriasis patients in our study had at least one episode of infection. This demonstrates that the prevalence of infection in these patients is not low. Using systemic steroids was associated with a higher risk of infection, while using methotrexate or infliximab was concomitant with a lower risk of infection.